Float converter model for wave power sources - Tokhmetova К.M.; Sholanov, K.S. (EAI Endorsed Transactions on Energy Web, 2017)
In the article it is proposed to improve wave power plants by using a primary manipulator converter (PMC) with the structure of a parallel six-mobile manipulator for converting energy of waves into mechanical energy. There has been developed a physical model of a primary manipulator converter confirming its functionality. There have been obtained geometrical dimensions of a primary manipulator converter and a float taking into account wave parameters. For selecting and analyzing the primary manipulator converter of wave power plants there are proposed the dependences for calculating power. The use of the primary manipulator converter in underwater wave power plants will permit to increase their reliability and efficiency in operation.